2016
DOI: 10.7554/elife.19127
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of X-linked gene expression during early mouse development by Rlim

Abstract: Mammalian X-linked gene expression is highly regulated as female cells contain two and male one X chromosome (X). To adjust the X gene dosage between genders, female mouse preimplantation embryos undergo an imprinted form of X chromosome inactivation (iXCI) that requires both Rlim (also known as Rnf12) and the long non-coding RNA Xist. Moreover, it is thought that gene expression from the single active X is upregulated to correct for bi-allelic autosomal (A) gene expression. We have combined mouse genetics wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 63 publications
(114 reference statements)
9
58
0
Order By: Relevance
“…Indeed, the formation of embryoid bodies more closely mimics the situation in blastocysts, and the finding that RLIM levels slightly increase during EB-differentiation (Fig. 2A) (Marks et al, 2015) is reminiscent of the increase in Rlim mRNA levels observed in early blastocysts, when the ICM forms (Wang et al, 2016). Moreover, we found that culturing differentiating ESCs in 7.5% O 2 levels had a general positive effect on Rlim -independent XCI efficiency (Fig.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Indeed, the formation of embryoid bodies more closely mimics the situation in blastocysts, and the finding that RLIM levels slightly increase during EB-differentiation (Fig. 2A) (Marks et al, 2015) is reminiscent of the increase in Rlim mRNA levels observed in early blastocysts, when the ICM forms (Wang et al, 2016). Moreover, we found that culturing differentiating ESCs in 7.5% O 2 levels had a general positive effect on Rlim -independent XCI efficiency (Fig.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, Xist clouds form specifically in the ICM of female blastocyst outgrowths with a maternal Rlim deletion (Δm) (Shin et al, 2010), consistent with a critical role for RLIM in iXCI but not rXCI. To exclude any influence of RLIM on rXCI, we examined Δm/Δp female blastocysts generated by crossing Δ/Y males with Sox2-Cre (SC) - cKO m /Δ p dams, which lack RLIM both in somatic tissues and germline (Wang et al, 2016). E4 blastocysts generated by this cross were cultured for 3 days and analyzed by RNA FISH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, XCI occurs rapidly, from the four cell stage, in rabbits it occurs from the early blastocyst stage, and in humans it occurs even later . In mice, XCU has been observed using RNA microarrays from the zygote stage and single cell RNA‐seq from the four cell stage . Thus XCU and XCI are temporally linked, suggesting a requirement for tight regulation of X dosage from very early in development in this species.…”
Section: Discussionmentioning
confidence: 97%
“…Initiation of both imprinted and random XCI is dependent on the Xist long noncoding RNA (lncRNA) that coats the future inactive X (Xi) chromosome in cis . The essential role of Xist in initiation of imprinted XCI has been recently highlighted in vivo using single cell or single embryo allele-specific transcriptome analyses in early pre-implantation development 7,8 . Xist RNA coating is followed by gene silencing and several epigenetic changes, such as the depletion of active chromatin marks ( eg tri-methylation of histone H3 Lysine 4 (H3K4me3), H3 and H4 acetylation), and recruitment of different epigenetic modifiers to the future Xi, including the polycomb repressive complex proteins PRC1 and PRC2, that result respectively in H2A ubiquitination and di-and tri-methylation of histone H3 Lysine 27 (H3K27me3) 9 .…”
Section: Introductionmentioning
confidence: 99%